Sex differences in mortality following isolated traumatic brain injury among older adults. Issue 3 (September 2016) - Albrecht, Jennifer S.; McCunn, Maureen; Stein, Deborah M.; Simoni-Wastila, Linda; Smith, Gordon S.
Abstract : BACKGROUND: Older adults have the highest rates of hospitalization and mortality from traumatic brain injury (TBI), yet outcomes in this population are not well studied. In particular, contradictory reports on the protective effect of female sex on mortality following TBI may have been related to age differences in TBI and other injury severity and mechanism. The objective of this study was to determine if there are sex differences in mortality following isolated TBI among older adults and compare with findings using all TBI. A secondary objective was to characterize TBI severity and mechanism by sex in this population. METHODS: This was a retrospective cohort study conducted among adults aged 65 and older treated for TBI at a single large Level I trauma center from 1996 to 2012 (n = 4, 854). Individuals treated for TBI were identified using International Classification of Disease, Ninth Revision, Clinical Modification ( ICD-9-CM ) codes. Isolated TBI was defined as an Abbreviated Injury Scale score of 0 for other body regions. Our primary outcome was mortality at discharge. RESULTS: Among those with isolated TBI (n = 1, 320), women (45% of sample) were older (mean [SD], 78.9 [7.7] years) than men (76.8 [7.5] years) ( p < 0.001). Women were more likely to have been injured in a fall (91% vs. 84%; p < 0.001). Adjusting for multiple injury severity measures, female sex was not significantly associated with decreased odds of mortality following isolated TBI (odds ratio, 1.01; 95% confidence interval, 0.66–1.54). Using all TBI cases, adjusted analysis found that female sex was significantly associated with decreased odd of mortality (odds ratio, 0.73; 95% confidence interval, 0.59–0.89). CONCLUSION: We found no sex differences in mortality following isolated TBI among older adults, in contrast with other studies and our own analyses using all TBI cases. Researchers should consider isolated TBI in outcome studies to prevent residual confounding by severity of other injuries. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level IV.